Nutritive assessment of selected browse forage species from Semi-arid environment of Nigeria using in vitro gas production technique - Njidda, A. A.; Al-Habib, I. K. (Nigerian Journal of Animal Science and Technology (NJAST), 2021)
The chemical composition and in vitro gas production of some browse species were evaluated. Crude protein (CP) content was highest (P<0.05) in Ceiba pentendra. Neutral detergent fibre, acid detergent fibre and acid detergent lignin were generally high ranging from 412.10 – 68810; 211.60 – 265.60 and 88.30 – 121.30 g kg-1 DM respectively. The total condensed tannins (TCT) was highest (P<0.05) in Celtis integuifolis. The values for phenolics, saponin and phytate were highest in Ceiba pentendrata, while Batryospermum paradoxum has the highest value for oxalate. In vitro gas production (GP) was lowest and highest in Analgeosus leocarpus (3.66 ml/200 mg DM) and Adansonia digitata (28.33 ml/200 mg DM) respectively. The GP from the insoluble but degradable fraction (b), potential gas production (a+b) and volume of gas produced (ml) at time t (Y) were highest in Adansonia digitata. The CP of browses weakly and positively correlated with incubation period at all hours and fermentation characteristics (a, b, a+b, c, t and Y). All the fibre fractions were negatively correlated with incubation periods and the fermentation characteristics. The secondary metabolites showed a weakly but negative correlation with fermentation characteristics.It can be concluded that the browse forages have nutritive potential as fodders for ruminants in a tropical environment.